A Case of Idiopathic Acute Pancreatitis in the First Trimester of Pregnancy - Tomomi Hara; Haruhiko Kanasaki; Aki Oride; Tomoko Ishihara; Satoru Kyo (Hindawi Limited, 2015)
Acute pancreatitis is rare in pregnancy, with an estimated incidence of approximately 1 in 1000 to 1 in 10,000 pregnancies. Acute pancreatitis in pregnancy usually occurs in the third trimester. Here, we report a case of acute pancreatitis in the first trimester. A 36-year-old primigravida at 11 weeks of gestation complained of severe lower abdominal pain. The pain gradually worsened and migrated toward the epigastric region. She had no history of chronic alcoholism. Blood investigations showed elevated level of C-reactive protein (9.58 mg/dL), pancreatic amylase (170 IU/L), and lipase (332 IU/L). There was no gallstone and no abnormality in the pancreatic and biliary ducts on ultrasonography. Antinuclear antibody and IgG4 were negative and no evidence of hyperlipidemia or diabetes was found. There was also no evidence of viral infection. On the third day of hospitalization, she was diagnosed with severe acute pancreatitis on magnetic resonance imaging. Medical interventions were initiated with nafamostat mesilate and ulinastatin, and parenteral nutrition was administered through a central venous catheter. On the eighth day of hospitalization, her condition gradually improved with a decreased level of pancreatic amylase and the pain subsided. After conservative management, she did not have any recurrence during her pregnancy.